Participação de crianças e de adolescentes nas tarefas domésticas - Adriana de França Drummond (2014)
This thesis has the general objective to investigate the participation of children and adolescents in house chores under three main axis: the predictive factors of the children and adolescents participation in house chores, the importance assigned by the caregivers and their satisfaction with child and adolescents participation in house chores and the child and adolescents learning process of house chores. Each of these structural axis of research was developed in the form of a paper. The first two were investigated from the caregivers point of view and used the instrument Children Helping Out: Responsibilities, Expectations and Supports (CHORES) to interview 109 caregivers of childrens and adolescents with typical development, from 6 to 14 years old, from families of various socioeconomic levels, living in Belo Horizonte (Minas Gerais, Brazil). The third study investigated the learning process of home participation of 13 children and adolescents under their own point of view, using semi-structured interviews. In the first research axis, a set of predictors for childs and adolescents performance, assistance provided by the caregivers and childrens and adolescents independence, especially regarding family care tasks, was identified by multiple regression models with a stepwise entry of variables. The performance of a larger number of tasks, the least assistance provided by the caregivers and the greater independence in family care tasks were outlined in families that did not have a house maid, in the group of children from 11 to 14 years old and in those whose mothers did not work outside their home. In this thesis second research axis, by means of quanti-qualitative methodology no significant correlation was observed between the importance and the satisfaction attributed by caregivers regarding their childrens participation in house chores (rs=0,04; p=0,699). It was observed that the majority of caregivers consider the participation of children and adolescents in household care as very important, attaching it especially to the future autonomy of the child and adolescent in adult life. As for the satisfaction, it was not as highly valued as the attached importance, being more closely related to the childs attitude towards participation than with the amount of tasks performed. There is an hiatus between the importance attributed to participation and the satisfaction of caregivers, showing an inconsistency between the ideal of future autonomy for the children and its implementation in daily life. In the third research axis, of qualitative nature, it is observed that the factors that enhance and challenge participation of children and adolescents in the house chores were established in their relation to the family and other participation contexts. The shared participation of all family members in house chores is an important motivator for children and adolescents. The lack of opportunity to perform the house chores and the lack of time resulting from school work overload and the extra-curricular activities restrain the participation of children and adolescents in house chores. Children and adolescents learn to participate and learn not to participate in the house chores, based on the possibilities to access permanence and on consistency of learning situations lived in daily life.